Jose Rizal biography, legacies, love life, and collaborations with other heroes - Mañebog, Jensen DG
"This book possesses the following distinctive features: 1. Includes new researches -- 2. Clarifies some controversies and discrepancies -- 3. Advocates e-learning and blended learning -- 4. With analyses, comments, and applications -- 5. Use blog and feature-article format -- 6. Features other Filipino heroes."--Prefa